Public Policies and Strategies for the Development of Research in Argentine Private Universities - Cecilia Adrogue; Ángela Corengia; Ana García de Fanelli; María Pita Carranza (Arizona State University, 2015)
The aim of this article is to analyze the extent to which quality assurance and government funding policies for research promoted changes in the research function at Argentine private universities. Based on the organizational approach applied to the study of university change, a case study was carried out. In order to identify the changing process, quantitative R D indicators were constructed; the statistical significance of their difference between periods was analyzed and a cluster analysis was performed. In addition, the influence of public policies on these changes was studied through the analysis of in-depth interviews with the universities' key informants and authorities, and the review of official and institutional documents. A tension in organizations' response was observed as they sought isomorphic changes to achieve compliance and legitimacy in their environment, but they also developed strategies in line with their own institutional mission, organizational resources and management and leadership skills. The results show that public policies have been effective at promoting research at those universities that showed an incipient development, and in the progressive consolidation at those that already had their mission aligned with the research university model.